Measurement of scapular medial border and inferior angle prominence using a novel scapulometer: A reliability and validity study. (December 2017) - Du, Wan-Yu; Huang, Tsun-Shun; Hsu, Kai-Chieh; Lin, Jiu-Jenq
Abstract: Background: Previous studies have proposed various ways to assess scapular dyskinesis. In clinic, assessment tools designed to measure the posterior displacement of the inferior angle of the scapula with reference to the posterior thoracic cage are needed. Objectives: A novel scapulometer was developed to measure scapular medial border and inferior angle prominence. Methods: A novel scapulometer was designed to measure the distance from the root of the spine (ROS) and the inferior angle (INF) of the scapula to the thorax wall in 29 participants with scapular dyskinesis bilaterally. Two raters measured the ROS and INF distance of the scapula 3 times bilaterally. Intraclass correlation coefficients (ICC) and standard error of measurement (SEM) were calculated to determine the inter-rater and intra-rater reliability. Validity was based on correlations (convergent: ROS and internal/external rotation, and INF and tilt; divergent: ROS/INF and upward rotation of the scapula) using a FASTRAK Polhemus 3-D motion tracking system assessing scapular tilt, internal/external rotation, and upward/downward rotation. Results: The average ROS and INF displacements were 13.7 ± 5.0 mm and 12.5 ± 6.3 mm, respectively. The results showed excellent intra-rater and inter-rater reliability, with ICC = 0.88–0.99 and 0.95–0.99 (SEM = 0.7–0.8 mm), respectively. Correlations were 0.35/0.19 (convergent validity) and 0.07/0.09 (divergent validity). Conclusions: The novel scapulometer has excellent reliability and fair validity to quantify medial border and inferior angle prominence of the scapula. Further research utilizing this instrument is recommended. Highlights: A novel scapulometer can reliably measure resting scapula position. Scapular winging can be characterized by medial border prominence measured by the novel scapulometer. The scapulometer measurement could quantify the degree of dyskinesis impairment.